A SYSTEMATIC LITERATURE REVIEW AND BIBLIOMETRIC ANALYSS OF WORK FAMILY CONFLICT - Rosyida, Abidatur; Sopiah (Transpublika Publisher, 2022)
The purposee of thiss systematicc literature revieww is to summarizeesome of theepublished research on the subject of family work. Conflict professionnFamilyyis an individual role that arises from the pressure of family roles and work role conflictss. This study aims to describe the impact of conflicttbetween jobssanddfamilies using the PRISMA method determined through bibliometriccanalysis. A total of 33 journals and 147 authors participated in screening journal results using the PRISMA method. The outcome variables related to work-family conflict are multi-role conflict, gender and mental health. Overall, the authors expect research resultssthisscan be useddas an ingredienttfutureewritten lessons and reflections.